2006
DOI: 10.1111/j.1399-3038.2005.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in intracellular cytokine profiles and Th2 dominance in allergic children

Abstract: The unbalanced T helper response has been pointed out in allergic diseases. Especially in childhood, it is important to consider the development of acquired immunity. We investigated the relationship between age and Th1, Th2, Tc1 or Tc2 cells. In addition, Th1, Th2, Tc1 or Tc2 cells in allergic diseases were compared with control subjects. Thirty-four healthy controls (0-40 years old), 200 samples of cord blood, nine patients with atopic dermatitis (AD) (1-3 years old) and five patients with bronchial asthma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
(35 reference statements)
3
23
0
3
Order By: Relevance
“…This is consistent with recent studies (36) that observed no toxicity in a syngeneic model in which C3H mice received CAR T cells expressing the murine equivalent of the CD19.IEVz CAR. A Th2 bias in humans was associated with aging (37), zinc deficiency (38,39), allergies (40,41), and lymphoma (42), and polymorphisms in Th2 genes, including the IL-10 promoter, were linked with an increased risk for developing non-Hodgkin lymphoma (43,44), suggesting that there are subgroups of people who may be more at risk for Th-2 cytokine-driven CAR T cell proliferation than others.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent studies (36) that observed no toxicity in a syngeneic model in which C3H mice received CAR T cells expressing the murine equivalent of the CD19.IEVz CAR. A Th2 bias in humans was associated with aging (37), zinc deficiency (38,39), allergies (40,41), and lymphoma (42), and polymorphisms in Th2 genes, including the IL-10 promoter, were linked with an increased risk for developing non-Hodgkin lymphoma (43,44), suggesting that there are subgroups of people who may be more at risk for Th-2 cytokine-driven CAR T cell proliferation than others.…”
Section: Discussionmentioning
confidence: 99%
“…This may be result from the diVerence of T cell immunity between children and adult. Kawamoto et al [11] presented that the CD4 or CD8 cells producing cytokines increased with age. Moreover, the percentages of Th1, Th2 and Tc1 showed a strong correlation with age in healthy controls [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Kawamoto et al [11] presented that the CD4 or CD8 cells producing cytokines increased with age. Moreover, the percentages of Th1, Th2 and Tc1 showed a strong correlation with age in healthy controls [4,11]. In our study, according to this concept, the diVerences in the immunological reaction to the streptococcal infection may induce the clinical diVerences between groups with normal and high ASO titers only in the patients with childhood psoriasis, not in the patients with adult psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion has been a number of findings describing various immune down-regulatory changes in patients with malignant disorders, including our work in human melanoma describing the dominance of T helper type 2 (Th2) systemic immune bias in patients with metastatic melanoma, as well as depletion of cytotoxic T lymphocytes (CTL) in sentinel lymph nodes downstream of invasive cutaneous melanoma [7,8]. Furthermore, other, smaller studies have associated ageing with an increase in Th2 cells with age in healthy volunteers and those with chronic allergic conditions [9].…”
Section: Introductionmentioning
confidence: 99%